HYDROGEOLOGICAL CHARACTERIZATION OF QUSHTAPA AND SHAMAMIK AREA IN ERBIL BASIN, USING PUMPING TEST DATA - Ameen, Seber M. M.; Dara, Rebwar N. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
This study investigates the hydrogeological parameters through detailed pumping test analysis in the Qushtapa and Shamamik areas within the Erbil Basin. This study aims to assess key aquifer parameters, including hydraulic conductivity, transmissivity, and storage coefficient, which are substantial for sustainable groundwater management. Data from 10 groundwater pumping tests were analyzed using established analytical approaches, such as the Cooper-Jacob straight-line method, and the Theis recovery method using AQTESOLV and the Microsoft Excel program to derive hydrogeological parameters of the aquifer. The results show significant spatial variability in aquifer properties impacted by lithological variability and the rate of groundwater recharge. The average hydraulic conductivity ranges between 0.0245 mday-1 and 0.191 mday-1. The average Transmissivity value ranges from 8.62 m2day-1 to 47.725 m2day-1. The Storage Coefficient ranges between 0.071 and 0.323. Based on the Krasny (1993) classification for Transmissivity, the studied area is classified as an area with a Low-Intermediate class of Transmissivity. Pumping tests play a crucial role in ensuring long-term water security and informing sustainable development policies in the study area.